Studies on Chemical Composition and Antioxidant Activity of Rudbeckia triloba - Zenovia Moldovan; Mihaela Buleandră; Eliza Oprea; Zamfirica Mînea (Journal of Analytical Methods in Chemistry)
The paper describes the physicochemical studies made on the decorative plant, Rudbeckia triloba (Asteraceae). For this purpose, essential oil, infusion, decoction, and hydroalcoholic macerate obtained from different aerial parts of Rudbeckia triloba were analyzed. The main phytochemical constituents identified by GC-MS analysis were found to be α-pinene (in dried leaves (46.0%) and flowers (40.1%)) and β-phellandrene (in essential oil of dried inflorescences (26.09%)). The Folin–Ciocalteu and quercetin assays revealed different values of total phenolic and flavonoid contents of petals, leaves, and seeds as a function of the solvent used and extraction procedure. The hydroalcoholic macerate of petals was found to present the maximum phenolic and flavonoid contents (130.29 ± 5.58 mg gallic acid equivalent/g dry vegetable material and 30.72 ± 1.35 mg quercetin equivalent/g dry vegetable material, resp.) and also exhibits the lower value of EC50 (0.32% (v/v)), obtained by applying the DPPH⋅ assay. Comparing the extraction methods applied, the maceration was found to be the most effective for phenolic compounds, most likely due to the solvent (70% ethanol). The use of water-alcohol mixture leads to an improvement of the extraction yield of phenolic compounds (including those with higher molecular weights) than by using water as extractive solvent, in the case of infusions and decocts.